Eigenvalue Problems : Algorithms, Software and Applications in Petascale Computing : EPASA 2015, Tsukuba, Japan, September 2015 /: Algorithms, Software and Applications in Petascale Computing : EPASA 2015, Tsukuba, Japan, September 2015. (2018) - Unknown
No abstract available